Speciation analysis of lead in marine animals by using capillary electrophoresis couple online with inductively coupled plasma mass spectrometry. Issue 9 (23rd December 2013) - Chen, Yiquan; Huang, Limei; Wu, Weihua; Ruan, Yajuan; Wu, Zujian; Xue, Zhimin; Fu, FengFu; Klampfl, Christian W.
<x xml:space="preserve">Abstract</x> We herein reported a environment‐friendly microwave‐assisted extraction used to extract trace lead compounds from marine animals and a ultrasensitive method for the analysis of Pb2+, trimethyl lead chloride (TML) and triethyl lead chloride (TEL) by using CE‐ICP‐MS. The extraction method is simple and has a high extracting efficiency. It can be used to completely extract both inorganic lead and organolead in marine animal samples without altering its species. The analytical method has a detection limit as low as 0.012–0.084 ng Pb/mL for Pb2+, TML, and TEL, and can be used to determine ultratrace Pb2+, TML, and TEL in marine animals directly without any preconcentration. With the help of above methods, we have successfully determined Pb2+, TML, and TEL in clam and oyster tissue within 20 min with a RSD (n = 6) < 5% and a recovery of 91–104%. Our results showed that Pb2+ was the main species of lead in clam and oyster, and organolead (TML) was only found in oyster. The proposed method provides a realistic approach for the accurate evaluation of lead pollution in seafood.